Media Environment in Georgia During the 2020 Elections - D. Abazov; N. Skvortsova (Проблемы постсоветского пространства, 2022)
Paper provides the analysis of state-owned and private media companies during parliamentary pre-election race in Georgia in 2020. An attempt to measure the influence of variously interpreted information by different media and how this process, precisely, affects elections was made in this work. It should be noted, the closer the elections are, the more aggressive and radical Georgian media-companies become in their relation to each other and to their audience on a whole.Political polarisation, as consequence of the fierce clash over political power, results in politization of all the social processes, and strongly affects information environment in Georgia. Despite following the democratic blueprint of state formation and announced course for the democratization of political processes, Georgian reality remains far distant from the set goals. Significant role in destabilization of the situation belongs to mass media, whose political activity prevents us from speaking about healthy political environment, nevertheless about flexible state-model in Georgia.